Optimization and Characterization of the Synthetic Secondary Chromosome synVicII in Escherichia coli - Messerschmidt, Sonja J.; Schindler, Daniel; Zumkeller, Celine M.; Kemter, Franziska S.; Schallopp, Nadine; Waldminghaus, Torsten (Frontiers in Bioengineering and Biotechnology, 2016)
Learning by building is one of the core ideas of synthetic biology research. Consequently, the way to fully understand what a chromosome is one needs to build more and more chromosomes. The last years have seen exciting synthetic-chromosome studies. We had previously introduced the synthetic secondary chromosome synVicII in E. coli. It is based on the replication mechanism of the secondary chromosome in Vibrio cholerae. Here we present a detailed analysis of its genetic characteristics and a selection approach to optimize replicon stability. We probe the origin diversity of secondary chromosomes from Vibrionaceae by construction of several new respective replicons. Finally we present a synVicII version 2.0 with several innovations including its full compatibility with the popular Modular Cloning (MoClo) assembly system.